Association of ABO blood group with survival following pancreatoduodenectomy for pancreatic ductal adenocarcinoma. Issue 11 (November 2020) - Williams, Hannah; Jajja, Mohammad R.; Hashmi, Salila S.; Maxwell, Daniel; Cardona, Kenneth; Maithel, Shishir K.; Russell, Maria C.; Sarmiento, Juan M.; Winer, Joshua H.; Kooby, David A.
Abstract: Background: Existing research suggests patients with blood group O are less likely to develop pancreatic ductal adenocarcinoma (PDAC) compared to those with non-O blood groups, and that survival from PDAC may be affected by ABO blood type. This study assessed survival outcomes in PDAC patients who underwent pancreatoduodenectomy (PD) in one health system. Methods: From 2010 to 2017, demographic, operative, chemotherapy and survival data for patients undergoing PD at Emory Healthcare were reviewed. Patients with blood type AB were excluded due to small sample size. The relationship between ABO blood group and survival was analyzed using Kaplan–Meier survival curves and multivariate cox proportional regression analysis. Results: Of 449 PDAC patients assessed, 204 (45.4%), 60 (13.4%) and 185 (41.2%) were blood groups A, B and O, respectively. Patients were well matched in clinicopathologic characteristics. Median survival did not differ by blood group (p = 0.82), and this relationship remained insignificant on cox regression analysis (p = 0.15). On multivariate analysis, lymph node positivity (p < 0.001) and increasing age (p = 0.001) were associated with reduced survival. Conclusion: In contrast to recent reports, this larger study found that blood group did not impact overall survival among patients undergoing PD for PDAC.